The neuroprotective role of CncC in a Drosophila model of Parkinson’s disease - Terence Al L. Abaquita; Milena Damulewicz; Elżbieta Pyza (PLoS ONE, 2025)
Parkinson’s disease (PD) is an incurable neurodegenerative disorder, yet significant advancements have been made in understanding its etiology. Among the risk factors, exposure to neurotoxins plays the greatest role. One of the most dangerous toxins is rotenone, a naturally derived compound that was historically used as an insecticide. This chemical affects mitochondrial function by blocking electron transfer, resulting in increased reactive oxygen species production and accumulation. Recently, the role of the Nrf2 pathway was explored as a possible protective mechanism to minimize the neurotoxic effects leading to Parkinson’s disease. Here, we used Drosophila melanogaster as a model to examine the link between the expression or activity levels of CncC (an ortholog of Nrf2) or HO (an ortholog of HO-1) in the brain and the detrimental effects of chronic exposure to rotenone. We found that flies with overexpression of CncC or silencing of ho survived better after exposure to rotenone compared with flies with partially suppressed CncC or upregulated ho expression. These experimental groups exposed to rotenone also exhibited significantly fewer degenerated dopaminergic (DA) neurons than did the wild-type group. Nevertheless, only those in which CncC was overexpressed in glia showed the best survival, the greatest percentage of climbing ability, and no effects on DA neurons. Our findings were supported by data obtained for flies fed with HO inhibitor (SnPPIX) or activator (hemin), as well as with curcumin (Nrf2 activator). The observed effects were connected with changes in autophagy and apoptosis pathways. Our data suggest that possible therapies exploiting Nrf2 activation should include restricting HO upregulation as a neuroprotective strategy against the toxic effects of rotenone.